Model Problem Posing dalam Pembelajaran Matematika: Sebuah Kajian Literatur Sistematik - Nurdin, Nurdin; Saiman, Saiman; Nurdin, Khaerani; Sardia, Sardia (Universitas Cokroaminoto Palopo, 2024)
The research aims to describe research results related to problem posing models in mathematics learning. This research uses a literature review method, with descriptive analysis and data obtained using secondary data. The research results are as follows: First; The problem posing approach influences learning outcomes and motivation to learn mathematics. Second; The problem posing approach is effective for improving critical thinking, creative thinking and abstract mathematical thinking skills. Third; Problem posing is effective for improving mathematical problem solving abilities. Fourth; Problem posing is effective for improving the ability to understand concepts. Five; Problem posing is effective for improving mathematical communication skills.